DOMESTIC ENERGY DEMAND AND CONSUMPTION BETWEEN TWO CONTRASTING COMMUNITIES IN GEREI LOCAL GOVERNMENT AREA, ADAMAWA STATE, NIGERIA: IMPLICATIONS FOR SUSTAINABLE ENVIRONMENTAL MANAGEMENT - UMAR, D.A; HALLIRU, S.L; MUHAMMAD, A.S; DAHIRU, R (FUDMA Journal of Earth and Environmental Sciences, 2024)
The problem of domestic energy demand and consumption between two contrasting communities, Sangere Village and Modibbo Adama University of Technology Yola (MAUTECH) Campus, in Gerei Local Government has been examined. The study aims to investigate whether the rate and choice of energy utilization of the two different communities will impact sound environmental management. Thus, they highlighted some of the socio-demographic factors that informed the choice of domestic energy types and the volume used as well as some environmental repercussions between these contrasting communities. Data was gathered using a questionnaire survey of 120 adult residents and was complemented by personal observation. The result indicates fuelwood was the highest energy utilized (30%) in the Sangere community, while the highest energy choice in MAUTECH community was cooking gas (27%). The implication of this perpetual fuelwood utilization, especially among Sengere residents will exacerbate deforestation, soil erosion, and air pollution, thereby undermining sustainable environmental management. Thus, a serious awareness campaign is urgently needed among Sangere residents where the literacy rate is low and population growth is visible. The study finally recommends government policies/legislation and public enlightenment/education as a panacea to attitudinal change for sound environmental management in the area.